2021
DOI: 10.3389/fphar.2021.715253
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Targeted Treatment of IgA Nephropathy: An Autoimmune Perspective

Abstract: Immunoglobulin (Ig) A nephropathy (IgAN) is the commonest form of primary glomerulonephritis worldwide and is, considered a significant cause of end-stage renal disease in young adults. The precise pathogenesis of IgAN is unclear. The clinical and pathological features vary significantly between individuals and races, which makes treating IgAN difficult. Currently, the therapeutic strategies in IgAN are still optimal blood pressure control and proteinuria remission to improve the renal function in most cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 125 publications
(135 reference statements)
0
21
0
Order By: Relevance
“…Encouragingly, targeted-release budesonide as a novel form of steroid therapy has been a research focus. Nefecon is an oral targeted release steroid, which mainly acts on the terminal ileum to exert immunosuppressive effects, and thereby the AEs of systemic steroid therapy are alleviated to some extent [ 2 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouragingly, targeted-release budesonide as a novel form of steroid therapy has been a research focus. Nefecon is an oral targeted release steroid, which mainly acts on the terminal ileum to exert immunosuppressive effects, and thereby the AEs of systemic steroid therapy are alleviated to some extent [ 2 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factor B (FB) is an essential component of complement activation by AP. LNP023 is an agent that can selectively block FB, thus preventing the complement activation by AP, which may contribute to alleviating disease progression [ 25 , 27 ]. OMS721 is an antibody targeting MASP-2, a protease involved in the complement activation by LP.…”
Section: Discussionmentioning
confidence: 99%
“…IgAN is an important cause of end-stage renal disease in young people. However, the disease cannot be treated effectively and selectively, and most treatment strategies are based on controlling blood pressure and relieving proteinuria to slow disease progression ( Leung et al, 2018 ; Huang and Xu 2021 ). Albuminuria is considered as the most widely and well-studied risk factor for IgAN progression to end-stage kidney disease ( Thompson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…IgA nephropathy is usually considered to be an immune complex-induced or polymerized IgA1-induced glomerulonephritis [57][58][59][60]. Zhong et al [61] reported that although α-diversity exhibited no significant differences in taxon richness and evenness, there was a clear separation in the composition of gut microbiota between patients with IgA nephropathy and healthy controls, indicating that the diversity of gut microbiota was altered in patients with IgA nephropathy.…”
Section: Iga Nephropathymentioning
confidence: 99%